Methods and Systems for Allocating and Reporting Indirect Costs in Management Accounting - Simeonova, R. (Економічний вісник Донбасу, 2015)
One of the main issues in management accounting, which has always been topical, and for which solutions are sought in its theory and practice, refers to the allocation and reporting of indirect costs. Indirect costs are an important element of cost under the current conditions. The paper discusses the importance of cost both in financial and management accounting - especially regarding cost management in different directions. Under the present conditions, there is an increase in the share of indirect costs in the cost of manufactured goods and services. This is inevitably associated with their allocation, which as a rule is provisional. The current paper studies the various methods and models of allocating indirect costs: the method of coefficients; the method of cost analysis centres and “Direct costing” system. The search for opportunities to improve the allocation of these costs is related to the Activity-based costing method (ABC). The paper studies the conceptual foundations and guidelines for its application. Одна з головних проблем у бухгалтерському та управлінському обліку, яка завжди була актуальною, і для якої рішення знаходяться в теорії і практиці, посилається на розподіл і повідомлення про постійні витрати. Постійні витрати - важливий елемент вартості за поточних умов. У статті обговорюється важливість вартості як у фінансовому, так і бухгалтерському та управлінському обліку - особливо відносно управління витратами. У сучасних умовах, має місце зростання частки постійних витрат у вартості промислових товарів і послуг. Це неминуче асоційоване з їх розміщенням, яке як правило тимчасове. У статті надано різні методи і моделі розподілу постійних витрат: метод коефіцієнтів, метод аналізу центрів витрат і "директ-кост" система. Пошук можливостей поліпшити розподіл прямих витрат є в сполученні з грунтованим на методі (АВС). Стаття вивчає концептуальні принципи і директиви для його застосування. Одна из главных проблем в бухгалтерском и управленческом учете, которая всегда была актуальной, и для которой решения ищутся в теории и практике, ссылается на распределение и сообщение о постоянных расходах. Постоянные расходы - важный элемент стоимости при текущих условиях. В статье обсуждается важность стоимости как в финансовом, так и бухгалтерском и управленческом учете - особенно относительно управления затратами. В современных условиях, имеет место рост доли постоянных расходов в стоимости промышленных товаров и услуг. Это неминуемо ассоциируется с их размещением, которое как правило временное. В статье приведены разные методы и модели распределения постоянных расходов: метод коэффициентов; метод анализа центров расходов и "директ-кост" систему. Поиск возможностей улучшить распределение прямых расходов состоит в сообщении с основанным на методе (АВС). Рассмотрены концептуальные принципы и директивы для его применения.